2008
DOI: 10.1523/jneurosci.0902-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Perceptual Learning in the Auditory Brainstem: Efferent Activity Predicts and Reflects Improvement at a Speech-in-Noise Discrimination Task

Abstract: An extensive corticofugal system extends from the auditory cortex toward subcortical nuclei along the auditory pathway. Corticofugal influences reach even into the inner ear via the efferents of the olivocochlear bundle, the medial branch of which modulates preneural sound amplification gain. This corticofugal system is thought to contribute to neuroplasticity underlying auditory perceptual learning. In the present study, we investigated the involvement of the medial olivocochlear bundle (MOCB) in perceptual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(188 citation statements)
references
References 62 publications
12
170
0
5
Order By: Relevance
“…Activation of the MEMR has been shown to reduce OAE amplitudes (Whitehead et al 1991). Many studies of MOC shifts using TEOAEs have therefore inferred the absence of MEMR activation by using noise levels that do not elicit the MEMR as assessed using standard clinical measurements employing a 226-Hz probe tone (e.g., Collet et al 1990;De Boer and Thornton 2008;De Ceulaer et al 2001). However, others have suggested that subclinical activation of the MEMR may be sufficient to impact measurement of MOC shifts (Feeney and Keefe 2001;Guinan et al 2003), which would limit the usefulness of clinical measurement criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the MEMR has been shown to reduce OAE amplitudes (Whitehead et al 1991). Many studies of MOC shifts using TEOAEs have therefore inferred the absence of MEMR activation by using noise levels that do not elicit the MEMR as assessed using standard clinical measurements employing a 226-Hz probe tone (e.g., Collet et al 1990;De Boer and Thornton 2008;De Ceulaer et al 2001). However, others have suggested that subclinical activation of the MEMR may be sufficient to impact measurement of MOC shifts (Feeney and Keefe 2001;Guinan et al 2003), which would limit the usefulness of clinical measurement criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have inferred lack of MEMR activation based on clinical immittance measurements (e.g., Collet et al 1990;De Boer and Thornton 2008;De Ceulaer et al 2001). However, it is possible that subclinical activation of the MEMR could confound or contaminate MOC shifts (Feeney and Keefe 2001;Guinan et al 2003).…”
Section: Stimulus Levelsmentioning
confidence: 99%
“…Previous reports of plasticity in the adult human auditory system have been generally limited to cortical measures of auditory processing. There is, however, increasing evidence that short-term training (de Boer and Thornton 2008;Song et al 2008) or short-term sensory deprivation (Munro and Blount 2009) can modify subcortical measures of auditory processing even in adulthood. The results of our study complement a growing body of research indicating that long-term experience in the discrimination and identification of pitch-evoking stimuli, obtained through the acquisition of a tone language or musical practice, modifies auditory processing at the level of the brainstem (see Tzounopoulos and Kraus 2009; Krishnan and Gandour 2009 for reviews).…”
Section: Subcortical Plasticity In the Auditory Systemmentioning
confidence: 99%
“…In a recent study, de Boer and Thornton (2008) found that activity of the medial olivocochlear bundle, which sends efferent signals from the brainstem to the cochlea, and is part of the corticofugal efferent system, reflected improvements on a speech in noise discrimination task after a period of auditory discrimination training. The corticofugal system, that projects from the auditory cortex to all major brainstem nuclei (Winer 2006), is likely to play a crucial role in subcortical plasticity.…”
Section: Subcortical Plasticity In the Auditory Systemmentioning
confidence: 99%
“…Descending neural pathways in the mammalian auditory system are believed to modulate the function of the peripheral auditory system [3,8,10]. These pathways include the medial olivocochlear (MOC) efferent innervation to the cochlear outer hair cells (OHCs) and the acoustic reflex pathways mediating middle ear muscle (MEM) contractions.…”
mentioning
confidence: 99%